Webs municipales del País Vasco y Navarra: Importancia de la dimensión de servicios y retraso en el aspecto informativo - Cantalapiedra González, María José; Genaut Arratibel, Aingeru; Peña Fernández, Simón; Pérez Dasilva, Jesús A. (Estudios sobre el Mensaje Periodístico, 2007)
Electronic administration finds its greatest potential at the local level since municipal councils are the institutions closest to the citizens. The three pillars on which this link is based are services, participation and local news. One of the main tools available to municipal councils for facilitating communication with citizens is their website. The efforts of these municipal portals are centred on the services and management dimension and on information about the workings of the municipal council. In this way, there is a certain lag with respect to the new forms of citizens’ participation, and advantage is not taken of synergies with the mass media of the locality, which affects the news offer.